Effect of Bleaching Gel Concentration on Tooth Color and Sensitivity: A Systematic Review and Meta-analysis - Pontes, M. M. A.; Gomes, J. M. L. [UNESP]; Lemos, C. A. A. [UNESP]; Leao, R. S.; Moraes, S. L. D.; Vasconcelos, B. C. E.; Pellizzer, E. P. [UNESP] (Operative Dentistry Inc, 2020)
Objective: The aim of this systematic review and meta-analysis was to evaluate a high concentration of hydrogen peroxide (35%) regarding tooth sensitivity and color change in tooth bleaching in comparison to low concentrations (6% to 20%). Methods and Materials: This review was conducted using the criteria of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and is registered on the Prospective Register of Systematic Reviews (CRD42017064493). The PICO question was Does a concentration of hydrogen peroxide >= 35% using in-office bleaching procedure contribute to greater tooth sensitivity? A search was made in PubMed/MEDLINE, Scopus, and the Cochrane Library. Results: Fourteen studies were selected for the qualitative analysis and seven for quantitative analysis. A total of 649 patients were evaluated (mean age: 36.32 years; range: 13.9 to 31 years), and the follow-up period ranged from one week to 12 months. The meta-analysis demonstrated that tooth sensitivity was higher in the patients submitted to treatment involving a high concentration of hydrogen peroxide (0.67; 95% confidence interval [CI]: 0.44 to 1.03; p=0.04; I-2: 56%), and a significant difference was found regarding objective color Delta E (1.53; 95% CI: 2.99 to 0.08; p<0.0001; I-2: 82%) but no significant difference was found regarding subjective color Delta SGU (0.24; CI: 0.75 to 1.23; p<0.00001; I-2: 89%). Conclusions: This study indicated that a lower concentration of hydrogen peroxide causes less tooth sensitivity and better effectiveness in objective color change (Delta E); however, there is no difference between them related to subjective color (Delta SGU).